INCREASING COUNTING BACKWARDS ABILITY IN AUTISTIC STUDENTS USING NUMBER CARD MEDIA - Azahra, Sabillah; Jaya, Indra; Winarsih, Murni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
The purpose of this study was to investigate the improvement of the ability to count backwards from 10 to 1 in students with autism using number card media. This research employed a quantitative approach with a Single Subject Research (SSR) experimental design, specifically the A-B-A design. The subject of the study was an autistic student in grade IV. Data collection was done through tests and observations. The data obtained were analyzed statistically and presented in tables and graphs. The results showed an improvement in the ability to count backwards from 10 to 1 in the student with autism after the intervention using number card media. The average score in baseline-2 showed a significant improvement compared to baseline-1 before the intervention. This result indicates that number card media can be used as a variation in learning in schools and can be beneficial for students with autism.